(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Business Environment, which involves both the micro and macro environment is highly influenced by global forces. These forces have a profound influence on the competitiveness of the business of an economy. It is imperative that an economy or a society adapts or tries to cope with the global forces. The niche of an economy is determined by the adaptive nature of the economy to the global forces that shape the nature and future of the business. The developing economies have to take into account the global forces in curving out their path of development. BRICS represents a group of developing and newly industrialized countries viz., Brazil, Russia, India, China and South Africa. It is imperative to understand the competitiveness of these four emerging economies. In this paper, an endeavor has been made to study the competitiveness level of these emerging economies with respect to the challenges posed by global forces. The study is based on secondary data from Global Competitiveness Report 2013-14, published by the World Economic Forum. The study will provide a vivid explanation of the importance of global forces shaping the future of business and how the developing countries are trying to cope with the changes and challenges posed by these forces.